Evidence-based core information for health communication of tobacco control: The effect of smoking on risks of female disease - Liu, Jin; Hao, Yun-Yi; Mao, Hui-Jia; Sun, Xiang-Ju; Huang, Xiao-Lu; Quan, Chen-Xin; Cao, Mei-Ling; Wei, Shu-Ting; Jin, Xue-Zheng; Wu, Yi-Bo (Frontiers in Public Health, 2022)
Objective Cigarettes have become the the biggest killer of contemporary female's health and beauty. What kind of health information is suitable for the general public is an important issue to be discussed globally. The purpose of this study is to generate systematic, rigorous, public-demand-oriented and appropriate core information relevant to tobacco control based on the best available evidence, combined with audience preferences and pre-dissemination content review from multidisciplinary expertise in order to improve the effectiveness of health communication of tobacco control. Methods Relevant systematic reviews meta-analysis that reported smoking on risks of female disease were identified by searching PubMed, Embase, the Cochrane Library, Web of Science, Clinical Trials.gov, and the International Clinical Trial Registry Platform. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) process was applied to assess the evidence in order to make rigorous core information. The audience prevalence survey was conducted to ensure that core information was targeted and tailored. Finally, the expert assessment was used for a pre-dissemination content review and to evaluate whether the core information was appropriate or not. Results The final core information consisted of eight parts concerning the effects of smoking and female cardiovascular disease, diabetes, rheumatoid arthritis, respiratory disease, digestive system disease, mental disease, non-pregnant female reproductive system disease, as well as pregnant women and their fetuses. A total of 35 items of core information suitable for dissemination was included and the quality of evidence, the degree of public demand and the outcome of pre-dissemination content review were reported. Conclusion The core information related to female cardiovascular system diseases, as well as liver cancer and upper gastrointestinal cancer is the preferred content for health communication of tobacco control. The quality of evidence for core information related to pregnant women and their infants, as well as diseases of reproductive system, respiratory system, and diabetes needs to be improved to meet high public demand. The core information related to mental disease is more suitable for dissemination to patients with mental illness than to the general public. Besides, dissemination of core information should be individualized. Evidence-based Core Information for Health Communication of Tobacco Control would be helpful to provide evidence support for health communication related to tobacco control and enhance public health literacy for international communities that have high smoking prevalence and related disease burden.